2014
DOI: 10.2147/ijn.s49297
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive liposomal drug delivery systems: state of the art review

Abstract: Thermosensitive liposomes are a promising tool for external targeting of drugs to solid tumors when used in combination with local hyperthermia or high intensity focused ultrasound. In vivo results have demonstrated strong evidence that external targeting is superior over passive targeting achieved by highly stable long-circulating drug formulations like PEGylated liposomal doxorubicin. Up to March 2014, the Web of Science listed 371 original papers in this field, with 45 in 2013 alone. Several formulations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(72 citation statements)
references
References 94 publications
0
68
0
2
Order By: Relevance
“…There have been many attempts to use chemical cues to trigger the target-specific release, such as acidic pH in the tumors, low endosomal/lysosomal pH, reductive intracellular environments, and tumor specific-enzymes (cathepsins, metalloproteases, etc.) [1416]. However, one should admit that the fidelity and robustness of these strategies might not be sufficient to achieve the desired goals.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many attempts to use chemical cues to trigger the target-specific release, such as acidic pH in the tumors, low endosomal/lysosomal pH, reductive intracellular environments, and tumor specific-enzymes (cathepsins, metalloproteases, etc.) [1416]. However, one should admit that the fidelity and robustness of these strategies might not be sufficient to achieve the desired goals.…”
Section: Introductionmentioning
confidence: 99%
“…Since hyperthermia also can increase cellular membrane fluidity, drug diffusion through the cell membrane can be increased. Early hyperthermia studies with passively targeted conventional and stealth liposomes revealed heating allowed more liposome extravasation, however the temperatures used were not sufficient for drug release within the tumor [25, 26]. These findings led to the design of thermosensitive liposomes which have been formulated to release their contents upon heating by incorporating lipids with phase transition properties in the heating temperature range, lysolipids or thermosensitive polymers [21, 23].…”
Section: Current Strategiesmentioning
confidence: 99%
“…Another problem has been low intratumoral penetration of the drug released from the liposome because of redistribution in the circulation following intravascular release [3, 7173]. Currently, several strategies are being investigated to improve liposome-based hyperthermia [25, 26]. These approaches include utilizing newer pegylated thermosensitive liposome and leucine zipper peptide-lipid hybrid formulations with improved in vivo drug retention and increased doxorubicin bioavailability in tumors [71, 73].…”
Section: Current Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…212 Temperature-sensitive liposomes have been also studied in vivo in guided hyperthermia treatment of cancer. 213,214 Liposomes containing a paramagnetic Mn 2+ salt or a Gd 3+ complex and doxorubicin have been tested to detect drug release. 215 …”
Section: Micelles and Liposomesmentioning
confidence: 99%